Tuberculosis and atypical mycobacterial infections in ruxolitinib-treated patients with primary or secondary myelofibrosis or polycythemia vera. (March 2019) - Lescuyer, Sylvain; Ledoux, Marie-Pierre; Gravier, Simon; Natarajan-Amé, Shanti; Duval, Céline; Maloisel, Fréderic; Mauvieux, Laurent; Toussaint, Elise; Fornecker, Luc-Matthieu; Herbrecht, Raoul
Highlights: Patients treated with ruxolitinib are at higher risk of mycobacterial infection. Tuberculosis under ruxolitinib can occur without any prior tuberculosis. Mycobacterial infections under ruxolitinib can occur early or late. Abstract: Ruxolitinib is a JAK-1/JAK-2 inhibitor indicated for the treatment of polycythemia vera and primary or secondary myelofibrosis. Only one patient (0.2%) was diagnosed with tuberculosis among the 485 patients receiving ruxolitinib in the four pivotal trials. Fourteen cases of tuberculosis have since been reported. We observed two (3%) mycobacterial infections (one due to Mycobacterium tuberculosis and one due to Mycobacterium avium complex) in our cohort of 65 patients receiving ruxolitinib. This observation suggests that the rate of mycobacterial infection might be higher than that observed in the pivotal trials and that atypical mycobacterial infections can also occur.